New brittle-stars (Echinodermata: Ophiuroidea) from New Zealand waters. - McKnight, D.G. (Zootaxa, 2003)
Thirteen new species of brittle-stars (Ophiuroidea: Echinodermata) and one new genus are described from the New Zealand region. These include: Ophiacanthidae (Ophiolebes); Ophiomyxidae (Ophiolycus, Renetheo n. gen.); and Ophiuridae (Amphiophiura, Ophiocten, Ophiophycis, Ophiura (Dictenophiura), Ophiura (Ophiuroglypha), Ophiomidas, and Ophiophyllum). Keys are provided to the described species of Ophiophycis and 4 closely related species of Amphiophiura occurring around New Zealand.